EFFECTIVENESS OF ONLINE MEDIA LEARNING FOR PHYSICAL EDUCATION IN SD TAMANSISWA JETIS, YOGYAKARTA - Fakhrurozi, Zaza Afnindar; Kristiyono (Jurnal Pendidikan Dasar dan Aktifitas Jasmani, 2025)
This research aims to find out how effective online learning is in the use of online media during the pandemic at SD Tamansiswa Jetis (Tamansiswa Jetis Elementary School), Yogyakarta City. This research was a descriptive quantitative study. The research method was the survey method with data collection techniques used the instruments in the form of questionnaires. The research population was all fifth and sixth grade students of SD Tamansiswa Jetis Yogyakarta, with the total of 40 students. The results of the research on the effectiveness of online learning media in Physical Education lessons at SD Tamansiswa Jetis Yogyakarta show the results with the various categories as follows: in the poor category at 32.5%, in the moderate category at 30%, in the good category at 22.5%, in the very good category at 10 %, and in the very poor category at 2.5%. These results indicate that the online learning using online media During the Covid-19 Pandemic for the fifth and sixth grade students in Physical Education subject at SD Tamansiswa Jetis, Yogyakarta City is not effective.